A Novel Method of Light Source Calibration under Near-field Lighting Condition. Issue 1 (May 2021) - Ge, Feng; Li, Chen; Zhang, Xu
Abstract: The paper presents a novel method of photometric stereo calibration that works under near-field condition, and eight LED lights are installed on the system. In order to estimate the pose of the light source, light source position estimation based on iPad imaging is proposed. However, it is difficult to estimate principal optical axis direction of the light source which would influence the reconstruction result. Considering the problems of above, the new convolution kernel is used to find the brightest point on the chessboard paper, and the principal optical axis direction of light source can be precisely calculated according to geometric transformation. The experiments show the high-quality of 3-D reconstruction can be obtained by using the novel calibration method.